Analisis Manajemen Ritel Berbasis Metode ARC dan TCR dalam Optimalisasi Produksi Harisma Home Industri - Dea Anisa br Bukit; Chindy Vepayosa Sitepu; Nazwa Helva; Najwa Inayah; Khansa Devatiha (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The study aims to improve the passion fruit syrup production system at Harisma Home Industry, which has been hindered by an inefficient facility layout and complicated raw material flow. These issues lead to longer processing time, higher operator workload, and reduced production capacity. To solve this, the research uses the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) to evaluate and redesign the layout. TCR results show that the Raw Material Warehouse has the highest priority with a score of 119, requiring an Absolutely Important (A) relationship with the Production Room. The Parking Area and Waiting Room also fall into the Absolutely Important category, as they support smooth movements of materials and visitors. Meanwhile, the Toilet has a Very Important (E) relationship with the Waiting Room due to comfort and accessibility needs. Based on these proximity requirements, a new layout was designed by placing the Raw Material Warehouse next to the Production Room to create a faster and more efficient material flow. Other facilities were rearranged to minimize unnecessary movement. This new layout is expected to streamline processes, reduce congestion, and enhance overall capacity and operational performance.